Pemetaan Masalah Dan Potensi Pengembangan Kawasan Setu Patok Kabupaten Cirebon - Muhfidlatul Qira’ati (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2022)
Cirebon Regency has the tourism potential of Setu Patok which should be taken into account as a tourist destination. The Setu Patok area has beautiful views, and the potential for wide green open space as a public open space area. Utilization of this tourism potential needs to be accompanied by efforts to develop villages around the reservoir, one of which is Sinarancang Village. The purpose of the study was to conduct an initial inventory of tourism potential and problems in the Setu Patok area as a development effort. Qualitative descriptive research method is used to present an overview of the area based on data triangulation. The results of the analysis are presented in a map of the potential for regional development. Sinarancang Village has a strategic location because it is close to Setu Patok. The potential for beautiful scenery and the potential for river tourism is the main attraction for Sinarancang Village. This initiation was initiated by building the Kabarong cafe business unit. Kabarong Cafe has an indoor and outdoor concept with beautiful views. BUMDES also develops home industries, namely mortar, brick, and crushed stone. However, the problem is that community participation is still minimal because the mindset they have is not a contributive mindset.